Characterization of Fe-hydrogenase genes diversity and hydrogen-producing population in an acidophilic sludge - Fang, H.H.P.; Zhang, T.; Li, C.
According to the DNA sequences of six Fe-hydrogenase genes (FHG)of Clostridium species retrieved from the GenBank, a set of primers specific for Fe-hydrogenase genes were identified from their common conserved regions. The length of DNA fragments amplified using these two primers averaged 313 bps. This primer set was then used to investigate the FHG diversity in an acidophilic rice-degrading sludge by methods based on polymerase chain reaction (PCR). Eight new Fe-hydrogenase gene fragments were identified from the sludge, as a result. Similarity based on amino acids among the 14 hydrogenase genes (8 newly found plus 6 known ones)was 39-97
Keywords: ACIDOPHILIC; FE-HYDROGENASE GENE; HYDROGEN PRODUCTION; PRIMER; QUANTITATIVE REAL-TIME POLYMERASE CHAIN REACTION